Evaluation of Cassava Starch Based Hydrogels for Sustained Release of Ampicillin - K. Athira, Geetha; Jyothi, Alummoottil N. (JOURNAL OF ROOT CROPS, 2017)
Hydrogels of native cassava starch, starch citrate, octenyl succinylated starch and composites of cassava starch with poly vinyl alcohol (PVA) as well as konjac glucomannan (KGM) have been evaluated as matrices for incorporating the antibiotic drug ampicillin to attain controlled release property. The hydrogels were characterized by scanning electron microscopy (SEM) and determination of physicochemical as well as rheological properties. For ST-PVA and ST-KGM hydrogels, storage modulus (GI) was greater than loss modulus (GlI ) indicating the more solid nature of the gels, whereas all other gels exhibited weak gel properties or more liquid nature since GII> GI. The swelling was maximum and erosion was lowest for the ST-KGM gel (184 ±0.4 at pH 2.1 and 171 ± 1.1 at pH 7.4) in acidic as well as alkaline medium. In vitro release studies carried out at different pH showed that ST-KGM gel exhibited more sustained release of ampicillin (77% and 59% respectively at pH 2.1 and 7.4) in comparison to other hydrogels.